Creating a food museum in Baan Saan, Phuket: A case study in material culture and media technology - Chaopreecha, Jakraphan; Tovankasame, Nicha (Humanities, Arts and Social Sciences Studies, 2023)
This study utilizes the lens of design anthropology to describe the phenomena which occurred when community members underwent a process to transform their house into a public museum. The researchers’ objective was to help the Baan Saan community, located near Phuket Old Town, develop a house museum. The research team decided to install embedded media technology—sensors and IoT technology—in the community space in order to display the historical background. Local foods were chosen to be the main topic of the exhibition. The community are historically Hokkien Chinese migrants, who brought their food recipes from China. The foods are not only local products on sale in the community, but also the result of a process which combines the utilization of local knowledge and the use of materials such as kitchenware, containers, and other equipment to prepare the ingredients. The authenticity of these foods depends on the process in which the knowledge about, and stories of, the materials are communicated. This study developed an innovative prototype media technology system to communicate the authenticity of the foods by linking them with the biographies of interrelated materials. Moreover, the prototype became an intermediary between community members, lab members, and visitors. This cooperation supports the possible future extension of the exhibition to other projects.